SOLVING A SYSTEM OF EQUATIONS USING THE POLAR COORDINATE SYSTEM (Лучшие интеллектуальные исследования, 2025)
Annotation: The article provides comprehensive information about the polar coordinate system and the generalized polar coordinate system. It presents a general understanding of the fundamental relationships between the polar and Cartesian coordinates of a point, along with several worked examples. The study explores how to solve various equations and systems of equations using the polar coordinate system. Additionally, a methodological recommendation is offered on using the polar coordinate system to enhance the effectiveness of teaching.